Biocompatible Calcium Ion-Doped Magnesium Ferrite Nanoparticles as a New Family of Photothermal Therapeutic Materials for Cancer Treatment - Panchanathan Manivasagan; Sekar Ashokkumar; Ala Manohar; Ara Joe; Hyo-Won Han; Sun-Hwa Seo; Thavasyappan Thambi; Hai-Sang Duong; Nagendra Kumar Kaushik; Ki Hyeon Kim; Eun Ha Choi; Eue-Soon Jang (MDPI AG, 2023)
Novel biocompatible and efficient photothermal (PT) therapeutic materials for cancer treatment have recently garnered significant attention, owing to their effective ablation of cancer cells, minimal invasiveness, quick recovery, and minimal damage to healthy cells. In this study, we designed and developed calcium ion-doped magnesium ferrite nanoparticles (Ca2+-doped MgFe2O4 NPs) as novel and effective PT therapeutic materials for cancer treatment, owing to their good biocompatibility, biosafety, high near-infrared (NIR) absorption, easy localization, short treatment period, remote controllability, high efficiency, and high specificity. The studied Ca2+-doped MgFe2O4 NPs exhibited a uniform spherical morphology with particle sizes of 14.24 ± 1.32 nm and a strong PT conversion efficiency (30.12%), making them promising for cancer photothermal therapy (PTT). In vitro experiments showed that Ca2+-doped MgFe2O4 NPs had no significant cytotoxic effects on non-laser-irradiated MDA-MB-231 cells, confirming that Ca2+-doped MgFe2O4 NPs exhibited high biocompatibility. More interestingly, Ca2+-doped MgFe2O4 NPs exhibited superior cytotoxicity to laser-irradiated MDA-MB-231 cells, inducing significant cell death. Our study proposes novel, safe, high-efficiency, and biocompatible PT therapeutics for treating cancers, opening new vistas for the future development of cancer PTT.